Evaluation of the Potential In Vitro effects of Plantago major L. on Wound Healing in Human Umbilical Vein Endothelial Cells (HUVEC) - Amalia, Latifa; Murwanti, Retno; Hertiani, Triana; Purnomo, Kurnia Rahayu (Indonesian Journal of Cancer Chemoprevention, 2024)
The treatment of skin wounds remains a major concern in the field of medicine, particularly in the case of chronic wounds resulting from various disorders such as diabetes. The utilization of herbs or herbal preparations for the purpose of healing skin wounds presents a therapeutic challenge within the realm of traditional medicine. Plantago major L. is known to have bioactive compounds that have wound healing activity such as aucubin. This study aimed to determine the in vitro wound healing potential of Plantago major L. extract (PLE). The study involved several assays, including phytochemical examination of PLE using TLC, cell viability testing using MTT assay, and wound healing testing using scratch assay on human umbilical vein endothelial cells (HUVEC). The results confirmed the presence of aucubin as one of the compounds in PLE. It was observed that PLE with 125 μg/mL exhibited the highest wound closure percentage at 90.66%. This study shows that PLE possesses wound healing capabilities.Keywords: Plantago major L., PLE, cytotoxic assay, wound scratch assay, HUVEC.